2020
DOI: 10.1029/2019wr026930
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive 2D and 3D Mapping of Root Zone Soil Moisture Through the Detection of Coarse Roots With Ground‐Penetrating Radar

Abstract: Root zone soil moisture (RZSM) is important in sustaining terrestrial ecosystems and water cycling. However, noninvasive mapping of RZSM remains challenging in the field, especially its spatial variability at local scales. We propose a novel method of applying ground-penetrating radar (GPR) for noninvasive determination of RZSM. First, this method identified coarse root reflections in GPR images to obtain the reflected wave velocity and soil water storage at various locations. Then, the horizontal distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 98 publications
(200 reference statements)
0
6
0
Order By: Relevance
“…Mapping RZSM is another RF application (Liu et al, 2020) where spatially varying RZSM is constructed from spatially distributed RZSM measurements. With the advent of an automatic ML implementation framework (Cai, 2020), Babaeian et al (2021) applied RF to generate high-spatial-resolution RZSM maps that capture the spatial variability of SM from physical and hydraulic soil properties and unmanned aerial system observations.…”
Section: In Rzsm Modelingmentioning
confidence: 99%
“…Mapping RZSM is another RF application (Liu et al, 2020) where spatially varying RZSM is constructed from spatially distributed RZSM measurements. With the advent of an automatic ML implementation framework (Cai, 2020), Babaeian et al (2021) applied RF to generate high-spatial-resolution RZSM maps that capture the spatial variability of SM from physical and hydraulic soil properties and unmanned aerial system observations.…”
Section: In Rzsm Modelingmentioning
confidence: 99%
“…In contrast, using crosshole GPR allows a direct link from the EM wave velocity to ε r (for more details, see Klotzsche et al, 2018). In recent years, surface GPR has been used to investigate the soil-plant continuum with large root systems such as tree roots (reviewed in L. Guo et al, 2013 andRodríguez-Robles et al, 2017) and shrub roots (e.g., Cui et al, 2021;Liu et al, 2020Liu et al, , 2019Parsekian et al, 2012). Although some studies investigated the possibility of estimating agricultural root systems (Delgado et al, 2017;Klotzsche, Lärm, et al, 2019;Liu et al, 2017;Wijewardana & Galagedara, 2010;Galagedara et al, 2002Galagedara et al, , 2003, the detection and mapping of finer root systems found in crops are still challenging using surface GPR.…”
Section: Core Ideasmentioning
confidence: 99%
“…Moreover, the characteristics of soil water change are not only controlled by internal factors such as soil texture and soil structure but also associated with external factors such as vegetation cover (Gao et al, 2020;Liu et al, 2020). Alpine meadow is one of the most important alpine ecosystem types on the Qinghai-Tibetan Plateau, covering approximately 700 000 km 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, observations of lysimeters in cold areas with freeze–thaw cycles, such as the Qinghai‐Tibet Plateau, will provide scientific data for soil water dynamics and their relationship with precipitation. Moreover, the characteristics of soil water change are not only controlled by internal factors such as soil texture and soil structure but also associated with external factors such as vegetation cover (Gao et al, 2020; Liu et al, 2020). Alpine meadow is one of the most important alpine ecosystem types on the Qinghai‐Tibetan Plateau, covering approximately 700 000 km 2 .…”
Section: Introductionmentioning
confidence: 99%